IMPLEMENTASI KLASIFIKASI BAYESIAN UNTUK STRATEGI MENYERANG JARAK DEKAT PADA NPC (NON PLAYER CHARACTER)MENGGUNAKAN UNITY 3D - Asmiatun, Siti; Hendrawan, Aria (Jurusan Teknologi Informasi Universitas Semarang, 2016)
In a game against the enemy attack strategy should be applied , making it more appealing game players to finish the game up with the objectives to beachieved. This study discusses the strategy of attacking at close range to the NPC (Non Player Character ). In a game , especially for FPS ( First Person Shooter ) , we need a strategy NPC , with the aim to make the game more attractive and realistic.Strike strategy in this research is to divide some of the behavior of NPCs attack when in the position closest to the enemy. This research applies Bayesian algorithm for classifying the behavior of the NPC attack. The classification is expected to improve the strategy against an enemy attack . NPC assault classification is divided into two offensive behavior is the behavior of hitting and biting behavior. As for the variables used in Bayesian classification is health points, attack points player and a distance obtained from NPC conditions. From the test results using testing method of Bayesian classification confusion matrix , with trial games 10 times , has resulted in the presentation level of accuracy in the confusion matrix reach a percentage of 80%. This proves that the behavior classification melee attack with Bayesian classification method can be applied with good results